Desarrollo de un sistema semiautomatizado de la planta de tratamiento de aguas residuales provenientes del área de tintorería de la empresa Textiles Texsa S.A. - Cunalata Guato, José Fernando (2020)
In the present work, a semiautomatic system for the control of the processes of residual water treatment was implemented, which fulfilled the function of eliminating a large amount of harmful agents that were present in the water discarded by the area of dyeing of the company "Textiles Texsa S.A.", this was done because with previous systems of treatment there were not significant changes in the characteristics of the water, in addition to the fact that these processes did not have tanks that fulfilled the necessary capacity of storage nor a control of their processes. In order to carry out an efficient treatment of residual water, it was chosen the combination of methods of; homogenization, electrocoagulation, chemical coagulation, chemical flocculation, sedimentation and filtration, interacting with the semiautomatic system, which used sensors and actuators for the control of these methods taking the water to the conditions required by the current norm [1] such conditions are; BOD5 of 170 mg/l, DQO of 350 mg/l, pH from 6 to 9 upH and temperature of 40°C. Finally, it was found that the processes carried out improved the characteristics of the residual water, obtaining as a result, a hydrogen potential of 6.35 to 7.87 upH, DBO5 of 41 to 286 mg/l, a DQO of 72.83 to 85 mg/l, while maintaining the current regulations limits [1].